Uric Acid in Inflammation and the Pathogenesis of Atherosclerosis - Yoshitaka Kimura (MDPI AG, 2021)
Hyperuricemia is a common metabolic syndrome. Elevated uric acid levels are risk factors for gout, hypertension, and chronic kidney diseases. Furthermore, various epidemiological studies have also demonstrated an association between cardiovascular risks and hyperuricemia. In hyperuricemia, reactive oxygen species (ROS) are produced simultaneously with the formation of uric acid by xanthine oxidases. Intracellular uric acid has also been reported to promote the production of ROS. The ROS and the intracellular uric acid itself regulate several intracellular signaling pathways, and alterations in these pathways may result in the development of atherosclerotic lesions. In this review, we describe the effect of uric acid on various molecular signals and the potential mechanisms of atherosclerosis development in hyperuricemia. Furthermore, we discuss the efficacy of treatments for hyperuricemia to protect against the development of atherosclerosis.